Examination of the "Theory of Guidance" in the View of 'Ali ibn Abi Talib (a): An Exploration into the Nahj Al-Balaghah. Issue 2 (3rd May 2016) - Rostami-Nasab, Abas Ali; Tajedini, Oranus; Sadatmoosavi, Ali
ABSTRACT: This study examines the "Theory of Guidance" according to 'Ali ibn Abi Talib (a). This theory is based on three divine covenants or fundamentals in guidance including the divine Prophet, the divine Book, and the divine human nature ( fitrat ). Research in this regard seems essential because this theory has not been previously considered or researched in the discipline of education. Research findings indicate that all three of the pedagogic fundamentals—namely the teacher, the student, and the subject matter —are essential elements in guidance. Education can be properly realized through the interaction of these constituents enabling attainment of a status worthy of humankind. It is important to note that the teacher, the student, and the subject matter each have their own place, and none can take the place of another. In this relationship, the teacher begins the educational process. It is the teacher who must understand the role of each of these elements and guide them wisely. In order to fulfill the process of education, the teacher must be prepared to receive guidance, understand the position and character of the student, and have a good command of the topic in a way that matches the nature and needs of the student.